Comparative Response of Organic and Fertilizer Source of Nutrients to Terminalia arjuna in Waterlogged - Sodic Soil - Singh, S. B. (Indian Forester, 2004)
A field experiment was conducted at Uppardaha village in Allahabad District of Uttar Pradesh , India to compare response of organic and fertilizer source of nutrients to Terminalia arjuna , planted on mound in waterlogged sodic soil. Four treatments applied with and without 10.0 g plant. , BHC were (i) Control , (ii) 2.0 kg plant-1 farm yard manure , (iii) 50 g plant-1 each of NPK through urea , single superphosphate and muriate of potash and (iv) farm yard manure plus NPK as treatment 2&3 , respectively. Experiment was conducted following Randomised Block Design in triplicate , Comparison of plant height recorded twice in a year uuder different treatments showed that farmyard manure had no response up to six months , started to maximize height after one year and resulted for significantly higher height after two years. Nutrients applied through urea , single super phosphate and muriate of potash resulted promising effect in the initial stage of growth but slowed down afterwards. After two and half years of treatment , maximum biomass was recorded in farmyard manure treated plants , which was followed by plants receiving farmyard manure plus fertilizers and fertilizers alone. Plants treated with farmyard manure showed maximum and control showed the minimum CBH and survival in plants. Application of BHC , though , increased survival and height of plants but difference in BHC treated and untreated plant was insignificant.